Community-based prevalence of typhoid fever, typhus, brucellosis and malaria among symptomatic individuals in Afar Region, Ethiopia. - Biruk Zerfu; Girmay Medhin; Gezahegne Mamo; Gezahegn Getahun; Rea Tschopp; Mengistu Legesse (Public Library of Science (PLoS), 2018)
BACKGROUND:In sub-Saharan Africa, where there is the scarcity of proper diagnostic tools, febrile illness related symptoms are often misdiagnosed as malaria. Information on causative agents of febrile illness related symptoms among pastoral communities in Ethiopia have rarely been described. METHODS:In this a community based cross-sectional survey, we assessed the prevalence of typhoid fever, typhus, brucellosis and malaria among individuals with a set of given symptoms in Amibara district, Afar Region, Ethiopia. Blood samples were collected from 650 study participants, and examined by Widal and Weilfelix direct card agglutination test (DCAT) as well as test tube based titration test for Salmonella enterica serotype Typhi (S. Typhi) and Rickettsia infections. Rose Bengal Plate Test (RBPT) and Complement Fixation Test (CFT) were used to screen Brucella infection. Thin and thick blood smears were used to diagnosis malaria. RESULTS:Out of 630 sera screened by DCAT, 83 (13.2%) were reactive to H and/or O antigens for S. Typhi infection. Among these, 46 (55.4%) were reactive by the titration test at the cut off value ≥ 1:80. The combined sero-prevalence for S. Typhi by the two tests was 7.3% (46/630). The seroprevalence for Rickettsia infection was 26.2% (165/630) by DCAT and 53.3% (88/165) by the titration test at the cut off value ≥ 1:80. The combined sero-prevalence for Rickettsia infection by the two tests was 14.0% (88/630). The sero-prevalence for Brucella infection was 12.7% (80/630) by RBPT, of which 28/80 (35%) were positive by CFT. The combined sero-prevalence for Brucella infection by the two tests was 4.4% (28/630). Out 650 suspected individuals for malaria, 16 (2.5%) were found positive for P. falciparum infection. CONCLUSION:In this study, typhoid fever, typhus, brucellosis and malaria were observed among symptomatic individuals. The study also highlighted that brucellosis cases can be misdiagnosed as malaria or other disease based solely on clinical diagnosis. Therefore, efforts are needed to improve disease awareness and laboratory services for the diagnosis of brucellosis and other zoonotic diseases to identify other causes of febrile illness in this pastoral setting.